Tectonic subsidence at a fault intersection and its control on sediment accumulation in the Bohai Sea, eastern China - Wenqin Jiang; Weiguo Hou; Hongxian Chu; Yuekai Hao; Wang Song; Meiling Yin; Qingtong Wang (Marine Geology, 2026)

Comparative Lipidomics and microstructural characterization of Milk fat globule membrane protein powders from bovine buttermilk and cheese whey - Kuolin Si; Mengxueyao Zhang; Xuexing Zong; Yin Pei; Lu Liu; Xiuxiu Zhang; Meiling Ge; Xiaodong Li; Qingquan Yan (Food Research International, 2026)

Rapid Detection of Spring Viremia of Carp Virus ( SVCV ) Using RAA ‐ CRISPR /Cas12a - Xiaoyang Li; Aoqing Zhang; Yingying Li; Yingying Wang; Hao Zheng; Defeng Zhang; Yan Ren; Xubing Mo; Yuting Deng; Junyu Luo; Meiling Yu; Bo Chen; et al. (Journal of Fish Diseases, 2026)
Spring viremia of carp virus (SVCV), that can infect cyprinoid and koi causing an acute hemorrhagic symptom, with a feature of widespread epidemic, which poses a severe threat to the global aquaculture industry. Given the absence of specific effective medicine or vaccines, the early, accurate diagnosis is critical in the disease prevention. Many SVCV detection methods have been established, but most require specialized equipment and skilled operators, which limits their field application. In this study, we established a recombinase‐mediated isothermal amplification (RAA) in conjunction with the CRISPR/Cas12a system targeting the screened conserved region of the G gene in the genome to identify SVCV. The optimal combination of the primer pairs and crRNA was screened via the fluorescence intensity. In addition, the test exhibited high sensitivity and specificity, which could detect at the limit of 1.243 × 10 1 copies/μL and show no cross‐reactivity with other common freshwater fish pathogens. Furthermore, the result could be visible by excitation of fluorophores by blue light at 39°C within 30 min. The integrated method combines the advantages of RAA and CRISPR‐based signal transduction, offering a diagnosis project in resource‐limited aquaculture environments and a field‐applicable early warning of SVCV.

Facet and crystallinity-dependent transformation of lepidocrocite impacts cadmium redistribution - Meiling Yin; Jin Wang; Songxiong Zhong; Xiaofei Li; Fei Huang; Chen Yang; Fangbai Li; Zhi Dang; Chuling Guo (Environmental Pollution, 2026)

Elevated CO2 synergizes with nanoplastics to intensify arsenic mobilization, biotransformation, and plant uptake in soil-spinach systems - Wei Li; Yabo Wang; Yuling Suo; Zishu Zheng; Qiao Xu; Meiling Xu; Fen Xu; Weiqin Yin; Shengsen Wang; Xiaozhi Wang (Environmental Pollution, 2026)

Interleukin-12 Supports Self-renewal Division of Mouse Hematopoietic Stem Cells in Polyvinyl Alcohol-Based Culture - Jinglei Zhai; Xialin Li; Meiling Yin; Sen Zhang; Xiaoming Liu; Lisha Wang; Nini Wang; Lin Wang; Hideo Ema; Fang Dong (Stem Cell Reviews and Reports, 2026)

Effects of doped Mn on ferrihydrite transformation and the associated arsenic behavior during sulfidation-reoxidation process - Kun Gao; Xudong Bai; Meiling Yin; Shuai Wang; Xingxing Wang; Juan Liu; Zhi Dang (Journal of Hazardous Materials, 2026)

Singlet oxygen-dominated dual-pathways catalytic ozonation of sulfamethoxazole over FeOx-N-BC/O3–MNBs system - Meiling Cai; Xiaojun Miao; Xiaoyan Wang; Xueyan Xue; Hui Zhu; Liping Yang; Xinqian Zhang; Jiao Yin (Journal of Environmental Chemical Engineering, 2026)

Tracing thallium pollution in arsenic mining/smelting areas using high-precision thallium isotopic composition - Xudong Wei; Shunlong Jiang; Jin Wang; Hangfei Guo; Dieyu Chen; Ke Lin; Meiling Yin; Wanpeng Chen; Yinyin Lu; Yurong Gao; Juan Liu (Applied Geochemistry, 2026)

A bacteriohopanetetrol stereoisomer in Western Pacific oxycline indicates anammox-driven nitrogen loss and warm eddy dynamics - Liqin Duan; Jinming Song; Meiling Yin; Xiaowei Wang; Chuanyu Liu; Jiawei Kan; Zhuoyue Wang; Feng Zhao; Xuegang Li; Huamao Yuan (Geochimica et Cosmochimica Acta, 2026)

Ecological distribution and functional characterization of polyethylene-degrading enzymes from diverse metagenomes - Ning Wang; Meiling Jin; Zixuan Zhu; Yuxin Wang; Xinyu Li; Jing Xu; Shijunyi Cheng; Yuanying Zhu; Ruiqi Wang; Tong Xu; Furong Yin; Xinyue Li; et al. (Science of The Total Environment, 2026)

Multi-mechanism collaborative photocatalytic CH4 conversion over Cu/ZnS/ZnOx-550 Z-scheme heterojunction - Weixin Li; Qing Liu; Zhongxuan Yin; Yongqing Ma; Ganhong Zheng; Chuhong Zhu; Zhenxiang Dai; Meiling Wang (Chemical Engineering Journal, 2025)

Grass-legume mixture optimizes soil new carbon sequestration by leveraging microbial necromass dynamics in a pear orchard - Qiao Xu; Yingdong Zhao; Meiling Xu; Jinlong Dong; Weiqin Yin; Jing Ma; Xiaozhi Wang (Agriculture, Ecosystems & Environment, 2025)

Bacteriochlorophyll reveals estuarine hypoxia and anoxygenic photosynthetic carbon fixation - Jiawei Kan; Liqin Duan; Jinming Song; Meiling Yin; Xuegang Li; Xiaoqi Liu; Huamao Yuan; Yingxia Wang (Limnology and Oceanography, 2025)
Bacteriochlorophylls (Bchls) are photosynthetic pigments produced by aerobic anoxygenic photosynthetic bacteria and anoxygenic photosynthetic bacteria. However, the sources, degradation, and influence of redox conditions in marine environments remain unclear. This study investigated the distribution of Bchls in the Changjiang Estuary to evaluate their origins, degradation, and environmental response. Results showed that total bacteriochlorophylls a (T Bchl a ), including bacteriochlorophyll a (Bchl a ) and its degradation product bacteriopheophytin a (Bphe a ), were higher in surface waters than in bottom waters in the inner estuary, where microbial evidence ( Sphingomonadaceae ) identified aerobic anoxygenic photosynthetic bacteria as the dominant source of T Bchl a . In contrast, the outer estuary exhibited elevated T Bchl a in bottom waters, with purple sulfur bacteria ( Chromatiaceae and Ectothiorhodospiraceae ) as the primary contributors. Significant negative correlations between Bphe a concentrations in bottom seawaters and surface sediments and the dissolved oxygen levels in bottom waters, along with a positive correlation between Bphe a in the surface sediments and the salinity difference between bottom and surface seawaters (Δ S ), suggest that Bphe a may serve as a useful indicator of hypoxia and water stratification. The contribution of anoxygenic photosynthetic bacteria to carbon fixation is expected to increase notably, potentially reaching 16% of phytoplankton carbon fixation after 100 years under expanding hypoxia. These findings establish Bchls as reliable indicators of hypoxia and water stratification and provide a framework for reevaluating carbon fixation in global hypoxic coastal systems.

Spatial distribution and risk assessment of microplastics in surface sediments in semi-enclosed waters: a case study of Laizhou Bay - Xuzhen Zhang; Hongxian Chu; Meiling Yin; Yadong Liu; Peng Chen; Qiangqiang Zhang; Xuejian Dai; Linghao Kong (Frontiers in Marine Science, 2025)
Marine ecosystems are the most important sinks for microplastics (MPs) from inland sources, and the input of large quantities of MPs into the oceans poses a serious threat to marine organisms and ecosystems. However, the characteristics of MPs contamination and its risk in semi-enclosed seas remain poorly understood. In this research, we conducted a comprehensive analysis and evaluation of the distribution patterns and ecological risks related to MPs found in the surface sediments of Laizhou Bay. We gathered surface sediments from various locations within the bay, which were then processed and analyzed to assess the MP content. According to the results, MPs in Laizhou Bay were widely distributed, with abundances ranging from 36–2125.5 items/g d.w. at different points, with an average of 534.7 items/g d.w. The MP forms were mainly fragments (61.91%) and particles (37.45%), with polyamide (PA) (32.73%), polyethylene terephthalate (PET) (12.42%), and polyurethane (PU) (10.81%) being the most dominant polymer types. MPs mainly originated from marine aquaculture, fishing, and domestic plastic waste; the contribution from marine activities was higher than that from land-based inputs, and their migration and dispersion were mainly affected by the hydrodynamics of water body exchange and intra-bay circulation. According to the pollution load index, the risk index of MPs in Laizhou Bay ranged from 1 to 7.68, indicating a low pollution level. However, the polymer risk index indicated that microplastic pollution in Laizhou Bay was at high risk, and PU and polyvinyl chloride were identified as the primary high-risk sources. This study systematically analyzed the composition, distribution, and multiple source characteristics of MPs in Laizhou Bay. The ecological risks associated with these MPs were assessed through the analysis of pollution load and polymer risk indices. This research offers a valuable dataset and a scientific foundation for understanding and managing MP pollution in semi-enclosed marine environments.

The behavior of NOM-Cu(Ⅱ)colloids at the goethite interface - Yuekang Chen; Lijuan Zeng; Kai Chen; Meiling Yin; Xiongkai Zheng; Yuting Zhou; Yanping Deng; Jiehong Ye; Zhi Dang; Chuling Guo (Water Research, 2025)

Respective contribution of varied reactive oxygen species formed in methane conversion over calcined ferric sulfate - Qing Liu; Weixin Li; Zhongxuan Yin; Yongqing Ma; Ganhong Zheng; Chuhong Zhu; Meiling Wang (Journal of Environmental Chemical Engineering, 2025)

Surface engineering of copper peroxide nanodots and Au nanozyme on porphyrin-based metal-organic frameworks induces cascade reactions for colorectal cancer treatment - Haoyu Chen; Rong Liu; Jiaxin Fu; Xiaohan Zhang; Xiaohua Zhu; Mingjie Wei; Feng Liu; Peng Yin; Haitao Li; Youyu Zhang; Meiling Liu; Juewen Liu (Chemical Engineering Journal, 2025)

Towards robust partial nitrification in low-ammonia wastewater: Electrospinning nanofiber composite-enhanced hydrogel beads immobilized comammox Nitrospira - Peng Tang; Liangang Hou; Meiling Yin; Feng Huang; Zhengwei Pan; Tianhao Shi; Jun Li; Yuhan Zhu; Xin Zhang; Peng Gao (Bioresource Technology, 2025)

Breast Cancer Bone Metastasis: Novel Prognostic Biomarkers Identified - Meiling Chu; Yan Zhang; Jie Chen; Hui Cong; Yulian Yin; Hongfeng Chen (Phenomics, 2025)

The distribution of nutrients and chlorophyll-a in the temperate coast of China: implications for marine ecological risks in the context of global warming - Dapeng Bai; Hongxian Chu; Yongcai Feng; Lixin Wang; Meiling Yin (Frontiers in Marine Science, 2025)
Introduction Nutrients directly regulate the level of primary productivity, which is crucial for the stability of marine ecosystems. However, under the context of human activities leading to global warming, factors influencing alterations in coastal nutrient dynamics remain a mystery. Methods A study was conducted to investigate the spatial distribution characteristics of nutrients and chlorophyll-a at 55 stations in the Bohai Bay region during the autumn of 2021. Results The dominant factor influencing coastal zone ecology in the surveyed area was identified as temperature. Multiple factors (e.g., riverine input, sediment release, atmospheric deposition, and hydrodynamics) collectively impacted nutrient dynamics. The temperature along the north-south transect was consistent, with a distinct demarcation at 118.68°E (19°C), where the temperature gradient exhibited a pronounced east-high, west-low pattern. The temperature difference between the surface and bottom waters was minimal. In the high-temperature eastern region, the redox potential was high (above 100 mV), and very few locations had low dissolved oxygen levels, indicating active aerobic microbial activity. This led to the decomposition of substantial organic matter, resulting in elevated ammonia-nitrogen concentrations, and low pH levels. The presence of ammonia-nitrogen promoted the growth and reproduction of planktonic organisms. Discussion Therefore, we are concerned that global climate warming may trigger changes, and even worsen, marine ecological environments in temperate coastal regions, necessitating heightened attention from researchers.

Characteristics and mechanisms of sea (salt) water intrusion in Laizhou City, Shandong Province, China - Linghao Kong; Hongxian Chu; Guohua Hou; Jiao Zeng; Liyuan Zhao; Xiangcai Han; Yachao Li; Faqiao Zhou; Meiling Yin; Xuzhen Zhang (Frontiers in Marine Science, 2025)
Sea (salt) water intrusion is a significant and ongoing geological disaster, and in recent years, it has become a notable concern for Laizhou City, Shandong Province. To identify the characteristics and mechanism of sea (salt) water intrusion in Laizhou City, samples of different types of water bodies (such as seawater, freshwater, slightly brackish water, brackish water, saline water, and brine) were systematically collected from the coastal zone area. The hydrochemical composition and evolution characteristics of the water bodies and the current situation, trends, and causes of sea (salt) water intrusion were analyzed. In 2020, the sea (salt) water intrusion reached 645.76 km 2 (including 151.64 km 2 of serious intrusion area), which is the largest ever recorded. The sea (salt) water intrusion had a strip-sheet distribution. From land to sea, groundwater gradually transitioned from the HCO 3 ·SO 4 ·Cl-Ca type to SO 4 ·Cl-Na·Ca and SO 4 ·Cl-Na types and then evolved to the Cl-Na type. Furthermore, from land to sea, the dominant cations and anions shifted from Ca 2+ and HCO 3 - to Na + and Cl - . The influence of seawater or brine gradually increased, that of Ca 2+ and HCO 3 - gradually decreased; whereas that of Cl - and Na + gradually increased, showing a division zone of freshwater → slightly brackish water → brackish water → saline water → seawater (brine) in the macroscopic territory. The freshwater, slightly brackish water, and brackish water bodies in the study area were controlled by evaporation and concentration processes and rock weathering leaching, whereas the saline water and brine were primarily controlled by evaporation and concentration processes. Groundwater salinity in the study area mainly originates from sea (salt) water intrusion, and locally groundwater salinity mainly originates from mineral dissolution or human activities. In addition, significant cation exchange adsorption occurred in slightly brackish and brackish water. Overall, these results will help to prevent and control seawater intrusions and improve disaster management.

Are there marine sedimentary losses and transgressions in the Southeast Bohai Sea during MIS 2-MIS 3? - Qingtong Wang; Gayan Bandara; Wenqin Jiang; Feifei Wang; Hongxian Chu; Meiling Yin; Chuanxiu Luo (Marine Micropaleontology, 2025)

Construct favorable solid electrolyte interphase by applying alternating current discharge during battery formation - Yulong Zhang; Shiyou Li; Meiling Wu; Lijuan Wang; Ning He; Yin Quan; Peng Wang; Dongni Zhao; Xiaoling Cui (Chemical Engineering Journal, 2025)

Correction to: Metanephric mesenchyme-derived Foxd1+ mesangial precursor cells alleviate mesangial proliferative glomerulonephritis - Meiling Jin; Zhong Yin; Kai Wei; Yuansheng Xie; Xueyuan Bai; Bo Fu; Zhe Feng; Qinggang Li; Xiangmei Chen (Journal of Molecular Medicine, 2025)

Influence of calcium carbonate on ferrihydrite bio-transformation and associated arsenic mobilization/redistribution - Bowei Zhang; Meiling Yin; Kun Gao; Zhi Dang; Chongxuan Liu (Environmental Pollution, 2025)

Birnessite enhanced Cr(III) oxidation during subsurface geochemical processes: Role of Mn(III)-induced nonphotochemical reactive oxygen species - Yuting Zhou; Chuling Guo; Yanping Deng; Yanjun Jiang; Meiling Yin; Kai Chen; Siyu Zhang; Guining Lu; Zhi Dang (Environmental Pollution, 2025)

Hypoxia exacerbate the marine ecological risk of arsenic: By stimulating its migration and release at the sediment-water interface - Liqin Duan; Jinming Song; Meiling Yin; Xiaoqi Liu; Xue Liu; Xuegang Li; Huamao Yuan (Water Research, 2025)

Effects of coexisting goethite or lepidocrocite on Fe(II)-induced ferrihydrite transformation pathways and Cd speciation - Meiling Yin; Xin Li; Chuling Guo; Qiaohui Zhong; Xiaofei Li; Lijuan Zeng; Yuting Zhou; Chen Yang; Zhi Dang (Science of The Total Environment, 2025)

Structural modifications of berberine and the lipid-regulating effects of its derivatives - Yun Lu; Mengxuan Yin; Yuting Lai; Xinyi Ye; Meiling Chen; Yubo Li (Medicinal Chemistry Research, 2025)

Investigation of the effects of polyethylene microplastics at environmentally relevant concentrations on the plant-soil-microbiota system: A two-year field trial - Meiling Xu; Wenqian Ma; Yu Yao; Qiao Xu; Wenchao Du; Ying Yin; Rong Ji; Xiaozhi Wang; Hongyan Guo (Science of The Total Environment, 2024)

Paleoenvironmental evolution and East Asian monsoon records through three stages of paleochannels since the mid-pleistocene in the Western Bohai Sea, North China - Shuyu Wu; Jun Liu; Hongxian Chu; Yongcai Feng; Meiling Yin; Lixin Pei (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Enhanced oxygen anions generation on Bi2S3/Sb2S3 heterostructure by visible light for trace H2S detection at room temperature - Meiling Yu; Jiayu Li; Dongmin Yin; Zhenze Zhou; Chenda Wei; You Wang; Juanyuan Hao (Journal of Hazardous Materials, 2024)

Elevated CO2 exacerbates the risk of methylmercury exposure in consuming aquatic products: Evidence from a complex paddy wetland ecosystem - Danni Wu; Lei Chen; Xueying Zong; Fan Jiang; Xiaojie Wang; Meiling Xu; Fuxun Ai; Wenchao Du; Ying Yin; Hongyan Guo (Environmental Pollution, 2024)

Mechanistic approach of tannery wastewater and sulfadiazine mutual toxicity in wheat (Triticum aestivum L.) and mitigation through exogenous application of gallic acid. - Muhammad Nafees; Muhammad Azhar Ali; Linlin Qiu; Ying Yin; Meiling Xu; Guobing Wang; Shafaqat Ali; Hongyan Guo (Chemosphere, 2024)

Evaluation of the JF5-based Aspergillus galactomannoprotein lateral flow device for diagnosing invasive aspergillosis in cancer patients - Lijuan Wan; Xueqin Cai; Meng Ling; Jinsong Kan; Meiling Yin; Huiyan Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Surface properties of schwertmannite with different sulfate contents and its effect on Cr(VI) adsorption - Chaoping Wang; Kai Chen; Meiling Yin; Yuting Zhou; Qinglin Zhuang; Qianqian Cao; Zhi Dang; Chuling Guo (Geochimica et Cosmochimica Acta, 2024)

STAT2 negatively regulates RIG-I in the antiviral innate immunity of black carp - Ji Liu; Chushan Dai; Lijun Yin; Xiao Yang; Jun Yan; Meiling Liu; Hui Wu; Jun Xiao; Weiguang Kong; Zhen Xu; Hao Feng (Fish & Shellfish Immunology, 2024)

Microbial features with uranium pollution in artificial reservoir sediments at different depths under drought stress - Siyu Liu; Juan Liu; Jingye She; Zhenyu Xie; Lei Zhou; Qunwei Dai; Xing Zhang; Yuebing Wan; Meiling Yin; Xinjiao Dong; Min Zhao; Diyun Chen; et al. (Science of The Total Environment, 2024)

Synchronized achieving amount reduction and efficiency increase of lithium salt-type additive by alternating current pulse discharge technology - Shiyou Li; Yulong Zhang; Shumin Wu; Yin Quan; Meiling Wu; Peng Wang; Dongni Zhao; Xiaoling Cui (Chemical Engineering Journal, 2024)

Vertical variations of bacteriohopanepolyols near the Changjiang Estuary waters: Implications for marine hypoxia and bacterial activities - Meiling Yin; Liqin Duan; Jinming Song; Jiawei Kan; Huamao Yuan; Xuegang Li; Yingxia Wang (Chemical Geology, 2024)

Unraveling seasonal shifts in microbial and geochemical mediated arsenic mobilization at the estuarine sediment-water interface under redox changes - Liqin Duan; Jinming Song; Yuting Zhang; Meiling Yin; Huamao Yuan; Xuegang Li (Science of The Total Environment, 2024)

Rice husk hydrochar prepared by hydrochloric acid assisted hydrothermal carbonization for levofloxacin removal in bioretention columns - Yidan Luo; Yuanwang Lan; Shuzhen Liang; Shuohan Yu; Mingshan Xue; Zuozhu Yin; Fang-Fang Shen; Xibao Li; Zhen Hong; Meiling Yan; Chan Xie; Bin Gao (Bioresource Technology, 2024)

Elevated CO2 alleviated the dissemination of antibiotic resistance genes in sulfadiazine-contaminated soil: A free-air CO2 enrichment study - Meiling Xu; Qian Xiang; Fen Xu; Lei Guo; Laura J. Carter; Wenchao Du; Chunwu Zhu; Ying Yin; Rong Ji; Xiaozhi Wang; Hongyan Guo (Journal of Hazardous Materials, 2023)

Pharmacokinetics and residue elimination of metalaxyl enantiomers in snakehead (Channa argus) - Hao Zhou; Meiyu Zhang; Qi Shan; Heqing Huang; Meiling Zhang; Shugui Liu; Jiawei Lin; Lisha Ma; Guangming Zheng; Lichun Li; Cheng Zhao; Xiaoxin Dai; et al. (Aquaculture, 2023)

North-south differences in hypoxia and nitrogen cycle of the East China Sea over the last century indicated by sedimentary bacteriohopanepolyols - Meiling Yin; Jinming Song; Liqin Duan; Huamao Yuan; Xuegang Li; Quancai Peng (Chemical Geology, 2023)

Elevated CO2 exacerbates effects of TiO2 nanoparticles on rice (Oryza sativa L.) leaf transcriptome and soil bacteria - Wenqian Ma; Wenchao Du; Kaihua Gu; Meiling Xu; Ying Yin; Yuanyuan Sun; Jichun Wu; Jianguo Zhu; Hongyan Guo (Science of The Total Environment, 2023)

Elevated CO2 aggravated polystyrene microplastics effects on the rice-soil system under field conditions - Meiling Xu; Qiao Xu; Guobing Wang; Wenchao Du; Jianguo Zhu; Ying Yin; Rong Ji; Xiaozhi Wang; Hongyan Guo (Environmental Pollution, 2023)

A colloidal aqueous electrolyte modulated by oleic acid for durable zinc metal anode - Meiling Wang; Xiaoyu Wu; Di Yang; Hainan Zhao; Li He; Jiaran Su; Xu Zhang; Xiuxiu Yin; Kangning Zhao; Yizhan Wang; Yingjin Wei (Chemical Engineering Journal, 2023)

Nonconservative behavior of dissolved molybdenum and its potential role in nitrogen cycling in the Bohai and Yellow Seas - Jinqi Fan; Liqin Duan; Meiling Yin; Huamao Yuan; Xuegang Li (Frontiers in Marine Science, 2022)
Molybdenum plays an important role in marine biological activity, especially in nitrogen cycling as a cofactor for N 2 fixation and nitrate reductase. However, the dissolved Mo (dMo) behavior and its interaction with N cycling in the coastal waters is still unclear. In this study, the dMo concentrations and parameters related to Mo distribution and N cycling in surface and bottom seawaters of the Bohai (BS) and Yellow Seas (YS) were examined. The results showed that dMo concentrations ranged from 36.4 nmol L -1 to 125.0 nmol L -1 , most of which deviated significantly from the conservative line, indicating nonconservative behavior of Mo relative to salinity. The highest dMo concentrations occurring in 36°N section of north of the South YS (SYS), were close to conservative value (105 nmol L -1 ). Significant depletion up to 40-50 nmol L -1 of dMo mainly appeared in the BS, NYS and south of the SYS, suggesting the possible removal of dMo by biological utilization and particle adsorption. Particularly, the increasing dMo concentrations away the Yellow River estuary indicated that freshwater dilution was one of reasons for dMo distributions in the BS. The similar spatial distribution of dMo and dissolved Mn concentrations suggested the possible scavenging by MnO x phases for Mo removal. The negative correlation between dMo and chlorophyll- a (Chl- a ) concentrations in surface seawaters suggested that biological uptake was involved in dMo removal. The depleted dMo in most of sites corresponded with the higher nitrite concentrations, implying the possible involvement of nitrate reduction process. Although the highest N 2 fixation rates and relative abundances of cyanobacteria appeared in 36°N section, corresponding with the conservative dMo, suggesting that Mo may play a minor role in N 2 fixation process there. The ten-folds of relative abundance of bacteria with nitrate reduction function than that with N 2 fixation function suggested that dMo seems to play more important role in nitration reduction than nitrogen fixation in the BS and YS.

Construction of mannose-modified polyethyleneimine-block-polycaprolactone cationic polymer micelles and its application in acute lung injury - Meiling Su; Heping Hu; Xuan Zhao; Chengyuan Huang; Bowen Yang; Zongning Yin (Drug Delivery and Translational Research, 2022)

Correction to: Reactive Oxygen Species–Responsive Celastrol-Loaded Bilirubin Nanoparticles for the Treatment of Rheumatoid Arthritis - Xuan Zhao; Chengyuan Huang; Meiling Su; Yu Ran; Ying Wang; Zongning Yin (The AAPS Journal, 2022)

Reactive Oxygen Species–Responsive Celastrol-Loaded Bilirubin Nanoparticles for the Treatment of Rheumatoid Arthritis - Xuan Zhao; Chengyuan Huang; Meiling Su; Yu Ran; Ying Wang; Zongning Yin (The AAPS Journal, 2022)

Integrated Assessment of Cd-contaminated Paddy Soil with Application of Combined Ameliorants: A Three-Year Field Study - Guobing Wang; Wenchao Du; Meiling Xu; Fuxun Ai; Ying Yin; Hongyan Guo (Bulletin of Environmental Contamination and Toxicology, 2021)

Epichloë endophyte infection enhances the tolerance of Stipa purpurea to parasitic stress through the regulation of antioxidants and phytohormones - Gensheng Bao; Meiling Song; Yuqin Wang; Yali Yin (Plant and Soil, 2021)

Ternary catalyst Mn-Fe-Ce/Al2O3 for the ozonation of phenol pollutant: performance and mechanism - Manning Zhang; Dulin Yin; Jinjin Guo; Huanghe Wu; Meiling Gong; Xiangdong Feng (Environmental Science and Pollution Research, 2021)

Dextran sulfate–modified pH-sensitive layered double hydroxide nanocomposites for treatment of rheumatoid arthritis - Xiahui Wang; Bowen Yang; Xiaowen Xu; Meiling Su; Mingrong Xi; Zongning Yin (Drug Delivery and Translational Research, 2021)

Divergence in response of japonica and hybrid rice to titanium dioxide nanoparticles - Meiling Xu; Lu Mao; Wenchao Du; Hongyan Guo; Ying Yin (Journal of Soils and Sediments, 2021)

Construction of Inflammatory Directed Polymer Micelles and Its Application in Acute Lung Injury - Jisen Zhang; Meiling Su; Zongning Yin (AAPS PharmSciTech, 2020)

Metanephric mesenchyme-derived Foxd1+ mesangial precursor cells alleviate mesangial proliferative glomerulonephritis - Meiling Jin; Zhong Yin; Kai Wei; Yuansheng Xie; Xueyuan Bai; Bo Fu; Zhe Feng; Qinggang Li; Xiangmei Chen (Journal of Molecular Medicine, 2019)

Experimental wave attenuation study over flexible plants on a submerged slope - Zegao Yin; Xiaoyu Yang; Yuanzhao Xu; Meiling Ding; Haixiang Lu (Journal of Ocean University of China, 2017)